The basic leucine zipper transcription factor OsbZIP83 and the glutaredoxins OsGRX6 and OsGRX9 facilitate rice iron utilization under the control of OsHRZ ubiquitin ligases - Kobayashi, Takanori; Shinkawa, Haruka; Nagano, Atsushi J.; Nishizawa, Naoko K. (The Plant journal : for cell and molecular biology, 2022)
SUMMARY Under low iron availability, plants induce the expression of various genes for iron uptake and translocation. The rice (Oryza sativa) ubiquitin ligases OsHRZ1 and OsHRZ2 cause overall repression of these iron‐related genes at the transcript level, but their protein‐level regulation is unclear. We conducted a proteome analysis to identify key regulators whose abundance was regulated by OsHRZs at the protein level. In response to iron deficiency or OsHRZ knockdown, many genes showed differential regulation between the transcript and protein levels, including the TGA‐type basic leucine zipper transcription factor OsbZIP83. We also identified two glutaredoxins, OsGRX6 and OsGRX9, as OsHRZ‐interacting proteins in yeast and plant cells. OsGRX6 also interacted with OsbZIP83. Our in vitro degradation assay suggested that OsbZIP83, OsGRX6 and OsGRX9 proteins are subjected to 26S proteasome‐ and OsHRZ‐dependent degradation. Proteome analysis and our in vitro degradation assay also suggested that OsbZIP83 protein was preferentially degraded under iron‐deficient conditions in rice roots. Transgenic rice lines overexpressing OsGRX9 and OsbZIP83 showed improved tolerance to iron deficiency. Expression of iron‐related genes was affected in the OsGRX9 and OsGRX6 knockdown lines, suggesting disturbed iron utilization and signaling. OsbZIP83 overexpression lines showed enhanced expression of OsYSL2 and OsNAS3, which are involved in internal iron translocation, in addition to OsGRX9 and genes related to phytoalexin biosynthesis and the salicylic acid pathway. The results suggest that OsbZIP83, OsGRX6 and OsGRX9 facilitate iron utilization downstream of the OsHRZ pathway. Significance Statement We identified new regulatory components of plant iron deficiency responses, the basic leucine zipper transcription factor OsbZIP83 and two glutaredoxins, OsGRX6 and OsGRX9, which facilitate rice (Oryza sativa) iron utilization. OsbZIP83, OsGRX6 and OsGRX9 interact with OsHRZ ubiquitin ligases and are subjected to OsHRZ‐dependent degradation via the 26S proteasome pathway, linking the protein‐level and transcript‐level regulation of iron deficiency responses downstream of OsHRZs.